Pengaruh Ketidakpastian Lingkungan Terhadap Kinerja Bisnis dengan Strategic Flexibility sebagai Variabel Mediasi - Fahmia Nurbaity (Jurnal Manajemen dan Kewirausahaan, 2017)
This purpose of this research is to identify and analyze the effect of environmental uncertainty on business performance, the effect of environmental uncertainty on strategic flexibility, and the effect of strategic flexibility to business performance. Strategic flexibility as a mediation variable. The design of this research is explanatory research. The research was conducted on the Small Real Estate Developers (REDs) in the region of Probolinggo. The analysis used is Partial Least Square (PLS). The variables in this study affect the observed variable and influenced by other variables without dealing directly with observable variables that uses second order. The results shows that there are influence between environmental uncertainty on business performance, environmental uncertainty on strategic flexibility, strategic flexibility to business performance, and strategic flexibility mediate environmental uncertainty on business performance. Nevertheless the mediating role of strategic flexibility in determining the magnitude of the influence of environmental uncertainty on business performance is smaller than the direct effect. The overall results of the study indicate that the combination of environmental uncertainty with complex state of uncertainty, effect uncertainty and response uncertainty underlies Small Real Estate Developers (REDs) in forming strategic flexibility, so it can correct or improve business performance.  https://doi.org/10.26905/jmdk.v5i1.1209